1997
DOI: 10.1577/1548-8659(1997)126<0961:rosits>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Splittail in the Sacramento–San Joaquin Estuary

Abstract: Splittail Pogonichthys macrolepidotus, an endemic cyprinid of the Sacramento-San Joaquin estuary, has been proposed for listing as threatened under the U.S. Endangered Species Act. Almost continuous low outflow conditions in the estuary from 1987 to 1994 led to reduced abundance of young splittails, but adult abundance did not decline consistently except in the downstream portion of the species' range. This range had decreased primarily as a result of historical levee and dam construction but did not appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 11 publications
6
89
0
Order By: Relevance
“…Similar to Sommer et al (1997), our salvage analyses suggest that entrainment patterns may be affected by year-class strength. Specifically, we found that the number of age-0 striped bass salvaged was well predicted (r ¼ 0.81) by their numbers in the TNS (Delta stations only) conducted by CDFG.…”
Section: Year-class Strengthmentioning
confidence: 54%
See 4 more Smart Citations
“…Similar to Sommer et al (1997), our salvage analyses suggest that entrainment patterns may be affected by year-class strength. Specifically, we found that the number of age-0 striped bass salvaged was well predicted (r ¼ 0.81) by their numbers in the TNS (Delta stations only) conducted by CDFG.…”
Section: Year-class Strengthmentioning
confidence: 54%
“…Few studies have examined patterns and mechanisms explaining fish losses at the CVP and SWP over the years (Stevens and Miller 1983;Stevens et al 1985;Brown et al 1996;Sommer et al 1997;Bennett 2005;Kimmerer 2008), despite the fact that they are two of the largest continuous fish sampling devices in the world. There have also been relatively few studies of the direct effects of water diversions from riverine and tidal ecosystems (Nobriga et al 2004;Moyle and Israel 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations